2000
DOI: 10.1021/cm000438y
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Assembly of Zeolite Nanoparticles into Ordered Macroporous Monoliths Using Core−Shell Building Blocks

Abstract: Latex beads are used as a combined template and porogen in the fabrication of monolithic silica containing a hierarchy of pores. Prefabricated core/shell particles, prepared by the layer-by-layer assembly of zeolite (silicalite) nanoparticles onto spherical latex templates, are assembled into macroscopic close-packed structures. Calcination removes all organic components and causes densification of the inorganic structure producing a macroporous zeolite in which both the pore size and wall thickness can be var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
202
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(202 citation statements)
references
References 38 publications
0
202
0
Order By: Relevance
“…Because the molecular size of polyolefins is larger than the pore size, cracking of polyolefins occurs mainly over the acid sites on the external surface, followed by the -20-formation of lighter olefins on the internal pore surface. Recently, hierarchical-structured zeolites have attracted attention because nano-pores (called as nanomorphic zeolite) [44,45] and meso-pores [46][47][48][49][50][51][52] are formed among nano-zeolite crystals. The hierarchical materials composed of nano-sized zeolites possess two main advantages: a large external surface area ascribable to nano-zeolite, and larger pores than the zeolitic pore allowing large molecules to reach active sites.…”
Section: Catalytic Reactionmentioning
confidence: 99%
“…Because the molecular size of polyolefins is larger than the pore size, cracking of polyolefins occurs mainly over the acid sites on the external surface, followed by the -20-formation of lighter olefins on the internal pore surface. Recently, hierarchical-structured zeolites have attracted attention because nano-pores (called as nanomorphic zeolite) [44,45] and meso-pores [46][47][48][49][50][51][52] are formed among nano-zeolite crystals. The hierarchical materials composed of nano-sized zeolites possess two main advantages: a large external surface area ascribable to nano-zeolite, and larger pores than the zeolitic pore allowing large molecules to reach active sites.…”
Section: Catalytic Reactionmentioning
confidence: 99%
“…[40] Consequently, considerable research efforts are dedicated to the design of novel routes for the preparation of zeolites with hierarchical pore structures, adjustable size and morphology, uniform crystallographic orientation, and ordered arrangement, [41][42][43] as these features are essential for emerging applications as advanced catalysts, chemical sensors, highly selective membranes, optical materials, and low dielectric materials for microelectronics. [44,45] Great success has been achieved on the control of hierarchical pore structure, size, and morphology of zeolite products [43,46,47] yet relatively less progress has been made on the alignment of the nanoor micro-zeolites into uniformly oriented and/or highly ordered arrays. [48] Xia et al [49] reported the first synthesis of 3D ordered arrays of nanozeolites with uniform size and crystallographic orientation, and adjustable overall shape by a simple hydrothermal coupled dissolution-reprecipitation pseudomorphic replacement route (Fig.…”
Section: Transformation Of Leucite (Kalsi 2 O 6 ) To Analcite (Naalsimentioning
confidence: 99%
“…4 However, as far as we know, there is only one report dealing with a solid including a trimodal pore system. 5 The described synthesis approaches are usually based on the use of so many different template agents as pore types. On the other hand, shaping of porous solids in the form of monoliths instead of fine powders (as usually produced) confers on them additional advantages and wide-ranging applications in catalysis.…”
mentioning
confidence: 99%
“…On the other hand, shaping of porous solids in the form of monoliths instead of fine powders (as usually produced) confers on them additional advantages and wide-ranging applications in catalysis. [5][6][7][8] Different research groups have been able to prepare zeolite monoliths with additional macroporous voids by using double scale template agents (small molecular templates and bacterial structures, polystyrene latex spheres or polyurethane foams as secondary large templates), and starting from solutions of inorganic precursors or, alternatively, from preformed zeolite nanoparticles as building blocks. 5,9,10 Polymer foams have been extensively used to synthesize ceramic foams of several compositions.…”
mentioning
confidence: 99%
See 1 more Smart Citation